Perbandingan Literasi Membaca dalam Sistem Pendidikan Dasar di Amerika Serikat dan Indonesia - Widyaswari, Tri (Jurnal Didaktika Pendidikan Dasar, 2025)
This research examines the comparison of education systems between the United States and Indonesia in the context of developing students’ reading literacy skills. Using a qualitative approach with comparative analysis methods, this study analyzes policy documents, research reports, and academic publications related to education systems and literacy programs in both countries. The research results show a significant gap in literacy achievement, as reflected in the 2021 PISA results with a difference of 141 points (US: 520, Indonesia: 379). Fundamental differences were found in educational system approaches, literacy program implementation, and supporting infrastructure. The United States, with its more decentralized federal system, demonstrates success through programs such as the Teachers College Reading and Writing Project (TCRWP), which resulted in an average 25% increase in student reading ability. Meanwhile, Indonesia has shown positive efforts through the School Literacy Movement (GLS) and Micro Credential Literacy Programs, although still facing challenges in implementation and quality equity. This research identifies the importance of continuous teacher professional development, provision of adequate infrastructure, and program adaptation that considers local context as key factors in improving literacy achievement.